Pathology of the outbreak of subgenotype 2.5 classical swine fever virus in northern Vietnam - Izzati, Uda Zahli; Hoa, Nguyen Thi; Lan, Nguyen Thi; Diep, Nguyen Van; Fuke, Naoyuki; Hirai, Takuya; Yamaguchi, Ryoji (Veterinary medicine and science, 2021)
Classical swine fever (CSF) is an endemic disease in southeastern Asia and is one of the most important swine diseases in Vietnam. This study was conducted to characterize the pathology of natural cases of CSF in northern Vietnam in 2018 and their genetic prevalence. A total of 10 representative pigs were collected from four provinces (Hung Yen, Ha Noi, Quang Ninh and Thai Binh) during five outbreaks and examined pathologically. The gross and histopathological findings showed the disease was expressed as the acute or the subacute to chronic form of CSF, depending on the age of the animals. The most consistently observed lesions associated with infection by the classical swine fever virus (CSFV) included lymphoid depletions in tonsils, lymph node and spleen; histiocytic hyperplasia in spleen; cerebral haemorrhage; perivascular cuffing in the brain; renal erythrodiapedesis; urothelial vacuolation and degeneration and interstitial pneumonia. The immunohistochemical findings showed a ubiquitous CSFV antigen mainly in the monocytes/macrophages and in the epithelial and endothelial cells in various organs. CSFV neurotropism was also found in the small neurons of the cerebrum and the ganglia of the myenteric plexus. Analysis of the full‐length envelope protein (E2) genome sequence showed that all strains were genetically clustered into subgenotype 2.5, sharing a nucleotide identity of 94.0%–100.00%. Based on the results of this study, the strain was categorized as a moderately virulent CSFV. In this study, natural cases of classical swine fever in northern Vietnam showed variable degree of lymphoid depletions in the lymphoid organs including lymph node, tonsil and spleen; with the remaining parenchyma replaced with reticulo‐histiocytic hyperplasia. This figure showed the sinus haemorrhage in the mesenteric lymph node and CSFV antigen was detected in the mononuclear cells by IHC.